2021
DOI: 10.1371/journal.pone.0248498
|View full text |Cite
|
Sign up to set email alerts
|

SARS-COV-2 comorbidity network and outcome in hospitalized patients in Crema, Italy

Abstract: We report onset, course, correlations with comorbidities, and diagnostic accuracy of nasopharyngeal swab in 539 individuals suspected to carry SARS-COV-2 admitted to the hospital of Crema, Italy. All individuals underwent clinical and laboratory exams, SARS-COV-2 reverse transcriptase-polymerase chain reaction on nasopharyngeal swab, and chest X-ray and/or computed tomography (CT). Data on onset, course, comorbidities, number of drugs including angiotensin converting enzyme (ACE) inhibitors and angiotensin-II-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 33 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…Similar findings were reported by the US Centers for Disease Control and Prevention (CDC) which revealed that 94% of ICU deaths occurred among patients with one or more underlying health conditions 20 . Our findings are also in line with prior Italian 21 , 22 and Chinese 23 , 24 studies, implying that interventions to safeguard individuals with pre-existing medical disorders should be implemented to reduce COVID-19-related deaths.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings were reported by the US Centers for Disease Control and Prevention (CDC) which revealed that 94% of ICU deaths occurred among patients with one or more underlying health conditions 20 . Our findings are also in line with prior Italian 21 , 22 and Chinese 23 , 24 studies, implying that interventions to safeguard individuals with pre-existing medical disorders should be implemented to reduce COVID-19-related deaths.…”
Section: Discussionsupporting
confidence: 89%
“…Patient age is considered as one of the important factors for hospitalization and mortality [ 18 ]. Irrespective of gender and ethnicity, older patients appear to be at higher risk of mortality than younger patients.…”
Section: Resultsmentioning
confidence: 99%
“…Along with machine learning techniques to predict the profile of hospitalized patients and the outcome, several works attempted to evaluate the contribution of comorbidities through a network approach ( Espinosa et al, 2020 ; Gili et al, 2021 ; Khedr et al, 2020 ; Mason et al, 2021 ). Comorbidity network analysis is a graph-theoretic approach to study associations from disease co-occurrence data.…”
Section: Introductionmentioning
confidence: 99%